Psychometric properties of the chemophobia scale: Ukrainian sample - DANYLIUK, Ivan; LYTVYN, Serhiy; MALYSHEVA, Karine; KURAPOV, Anton; YAHIIAIEV, Illia; LOSHENKO, Oleksandra (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The problem of chemophobia, which refers to an irrational fear of chemicals, is a relatively new phenomenon that is gaining attention in scientific circles. This fear can manifest in various aspects of daily life, impacting people’s attitudes towards food additives, pharmaceuticals, and vaccines. Understanding the nature and extent of chemophobia is essential for addressing these fears effectively. This study aimed to adapt the Chemophobia Scale, originally developed in English, into Ukrainian. Methods. The study involved 392 respondents from diverse regions across Ukraine, encompassing a wide demographic range to ensure representativeness. Participants were recruited using both online and offline methods. The psychometric properties of the Ukrainian version of the Chemophobia Scale were assessed using comprehensive statistical analyses. These analyses included Cronbach’s alpha to measure internal consistency, exploratory and confirmatory factor analyses to assess the scale’s structure, and a correlation matrix with the Multidimensional Health Locus of Control (MHLC) scale to examine construct validity. Results. The Cronbach’s alpha for the Ukrainian version of the Chemophobia Scale was 0.84, indicating a high level of internal consistency comparable to the original scale. Exploratory factor analysis suggested the possibility of using both one-factor and two-factor structures for the scale. However, the one-factor structure was deemed more acceptable in terms of indicator reliability and consistency with the original model. The fit indices for the one-factor model were as follows: x2 = 100, P < 0.001; Comparative Fit Index (CFI) = 0.919; Tucker-Lewis Index (TLI) = 0.878; Standardized Root Mean Square Residual (SRMR) = 0.05; Root Mean Square Error of Approximation (RMSEA) = 0.125. The correlation analysis revealed a significant relationship between scores on the Chemophobia Scale and specific items on the MHLC scale, particularly those related to ’chance’ and ’internal’ health control beliefs. Conclusions. The adapted Ukrainian version of the Chemophobia Scale demonstrated satisfactory psychometric properties, indicating its suitability for use in Ukrainian-speaking samples. This, in turn, can inform targeted interventions to address irrational fears related to chemicals, thereby improving public health outcomes.